ChemInform Abstract: Preparation, Crystal Structure, Electronic Structure, Impedance Spectroscopy, and Raman Spectroscopy of Li3SbS3 and Li3AsS3. Issue 12 (14th March 2013) - Huber, Sebastian; Preitschaft, Christian; Weihrich, Richard; Pfitzner, Arno
Abstract Single crystals of Li3AsS3 are prepared by a new route involving LiI as a flux.